Existencialismus a sociologie: Velké míjení a pozdní setkávání - Petrusek, Miloslav (Lidé města, 2011)
This article follows two aims: to inform and to analyse. It demonstrates how the topics elaborated by classical French and German schools of existentialism have been spontaneously mixed, and, at the same time, disregarded since the 1950's. It also shows how these topics later started to reappear in the newly constituted „sociology of everyday life". The overall aim of this study is to provide a plastic account of the themes and the authors (especially from the field of philosophy) that significantly influenced the development of sociological thinking in the late 20th century. It is also indicated that this „existential urgency" has not disappeared from sociology, and we can find distinct traces of it in various accounts of social life even today.